A Beam Design Aid for Structural Tubing - Geschwindner, Louis F. (Engineering Journal, 2010)
The 2005 AISC Specification includes a stiffness reduction factor, Ï„b, in Appendix 7 to be used in the direct analysis method to account for the presence of residual stresses and their influence on the second order effects of frame behavior. The 2005 Commentary includes a stiffness reduction factor, Ï„a, to be used along with the effective length nomograph to account for the influence of column inelasticity due to residual stresses on effective length. These two stiffness reduction factors are intended to account for the same effect yet they are different. This paper provides the background for these two factors, and it will demonstrate that Ï„b is the more correct stiffness reduction factor. The 2010 AISC Specification will recommend its use with both the direct analysis method and the effective length nomograph.